1999
DOI: 10.1016/s0741-5214(99)70189-8
|View full text |Cite
|
Sign up to set email alerts
|

Association of smooth muscle cell phenotypic modulation with extracellular matrix alterations during neointima formation in rabbit vein grafts

Abstract: The neointima in the vein graft was formed initially by means of migration and proliferation of the phenotypically modulated, dedifferentiated-type SMCs and continued to thicken by means of sustained ECM accumulation, including type I collagen and decorin, in association with the prolonged presence of the dedifferentiated-type SMCs. These chronologic features in cell kinetics and ECM accumulation may contribute to the frequent occurrence of graft wall thickening that occurs in the vein grafts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 42 publications
4
23
0
2
Order By: Relevance
“…The observed alteration in SMC phenotype that resulted from exposing PIJVs to ART conditions agrees with previously reported data [71,131,163]. The concept of more gradual imposition of arterial levels of CWS to AVGs has not previously been reported but could result in a means to slow down or inhibit SMC phenotypic modulation which could consequently attenuate the hyperplastic response.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The observed alteration in SMC phenotype that resulted from exposing PIJVs to ART conditions agrees with previously reported data [71,131,163]. The concept of more gradual imposition of arterial levels of CWS to AVGs has not previously been reported but could result in a means to slow down or inhibit SMC phenotypic modulation which could consequently attenuate the hyperplastic response.…”
Section: Discussionsupporting
confidence: 90%
“…Balloon inflation injury to the media was shown to promote ECM synthesis by SMCs as well as to decrease alpha actin content [162]. Several reports have shown that neointimal SMCs of veins transposed to the arterial circulation are phenotypically altered [71,131,163], supporting the notion that the change from the venous to the arterial environment triggers phenotypic alteration. Further evidence comes from ex vivo organ culture studies where, for example, cyclic stretch was found to be necessary to maintain the contractile function of SMCs in cultured rat portal veins [164].…”
Section: Phenotypic Modulationmentioning
confidence: 89%
See 2 more Smart Citations
“…For example, balloon inflation injury to the media was shown to promote extracellular matrix synthesis and decrease ␣-actin content in SMCs [156]. Zhang et al showed that neointimal smooth muscle cells of external jugular veins transposed to the carotid artery position display a more primitive synthetic phenotype [157], supporting the notion that the change from the venous to the arterial biomechanical milieu triggers phenotypic alteration. Further evidence comes from ex vivo organ culture studies wherein cyclic stretch was found to be necessary to maintain the contractile function of SMCs in cultured rat portal veins [158].…”
Section: Lipid Accumulationmentioning
confidence: 98%